Effects of a preseason neuromuscular training program vs. an endurance-dominated program on physical fitness and injury prevention in female soccer players - Belamjahad, A.; Tourny, C.; Jebabli, N.; Clark, C. C. T.; Laher, I.; Hackney, A. C.; Granacher, U.; Zouhal, H. (Sports Medicine - Open, 2024)
Background The pre-season preparatory period is considered key for optimizing the physical fitness levels needed to withstand congested match periods and preventing injuries during the regular soccer season. This study contrasted the effects s of neuromuscular training (NMT) versus an endurance-dominated training (ET) program conducted during the preseason on measures of physical fitness and injury occurrence in female soccer players.